Analisis Fasilitas Ruang Tunggu Terhadap Kepuasan Penumpang Diterminal Bandar Udara Internasional Raja Haji Fisabilillah Tanjungpinang Dengan Metode Customer Satisfaction Index (Csi) - Christian Lydia Sihaloho; Andi Syaputra (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
The higher the competition in the same field, airports must always pay attention to what are the needs and expectations of service users. One of the needs and expectations of aviation service users is airport facilities. Airports are required to always pay attention to facilities in order to provide satisfaction to their customers. The purpose of this study is the waiting room facility for passenger satisfaction at the terminal of Raja Haji Fisabilillah Tanjungpinang International Airport With the Customer Satisfaction Index (CSI) Method This study used quantitative methods using the Customer Satisfaction Index (CSI) Method to measure passenger satisfaction and data collection techniques in the form of questionnaires. The number of samples was 88 people using the slovin formula. The analysis was performed using, validity test, reliability test, simple linear regression, T Test and Coefficient of Determination Test (R2). There is an influence of the waiting room facility (X) on the satisfaction of the patronage (Y) of Raja Haji Fisabilillah Tanjungpinang International Airport significantly with a sig0.000 value < 0.05. Based on the calculated t value, it is known that the t value is 12.696 > 1.988 so it can be concluded that the variable X or independent affects the variable Y or so that Ha is accepted. The Costomer Satisfaction Index (CSI) value is 43.56%, based on this, the passenger satisfaction score is included in the fairly satisfied scale. This passenger satisfaction is renewed by the obstacles that exist in the waiting room facilities of Raja Haji Fisabilillah Tanjungpinang Airport.